Cis‐Regulatory variation affecting gene expression contributes to the improvement of maize kernel size. (30th July 2022) - Li, Yong‐xiang; Lu, Jiawen; He, Cheng; Wu, Xun; Cui, Yu; Chen, Lin; Zhang, Jie; Xie, Yuxin; An, Yixin; Liu, Xuyang; Zhen, Sihan; Liu, Yunjun; et al.
SUMMARY: cis ‐Regulatory variations contribute to trait evolution and adaptation during crop domestication and improvement. As the most important harvested organ in maize ( Zea mays L.), kernel size has undergone intensive selection for size. However, the associations between maize kernel size and cis ‐regulatory variations remain unclear. We chose two independent association populations to dissect the genetic architecture of maize kernel size together with transcriptomic and genotypic data. The resulting phenotypes reflected a strong influence of population structure on kernel size. Compared with genome‐wide association studies (GWASs), which accounted for population structure and relatedness, GWAS based on a naïve or simple linear model revealed additional associated single‐nucleotide polymorphisms significantly involved in the conserved pathways controlling seed size in plants. Regulation analyses through expression quantitative trait locus mapping revealed that cis ‐regulatory variations likely control kernel size by fine‐tuning the expression of proximal genes, among which ZmKL1 (GRMZM2G098305) was transgenically validated. We also proved that the pyramiding of the favorable cis‐ regulatory variations has contributed to the improvement of maize kernel size. Collectively, our results demonstrate that cis ‐regulatory variations, together with their regulatory genes, provide excellent targets for future maize improvement. Significance Statement: GWAS associations confounded with population structure and relatedness were found to contribute to the genetic architecture of maize kernel size. Meanwhile, the favourable cis‐regulatory variations were found to involve in the improvement of maize kernel size.